In-Hospital Mortality by Race and Ethnicity Among Hospitalized COVID-19 Patients Using Data From the US National COVID Cohort Collaborative - Antonije Lazic; J. Mick Tilford; Bradley C. Martin; Mandana Rezaeiahari; Anthony Goudie; Ahmad Baghal; Melody Greer (American Journal of Medicine Open)
Background: Studies examining racial and ethnic disparities in-hospital mortality for patients hospitalized with COVID-19 had mixed results. Findings from patients within academic medical centers (AMCs) are lacking, but important given the role of AMCs in improving health equity. Objective: The purpose of this study is to assess whether minority patients hospitalized with COVID-19 in National COVID Cohort Collaborative (N3C) institutions, which consist predominantly of AMCs, have higher mortality rates relative to White patients. Design: A retrospective analysis of patients hospitalized with COVID-19 was performed. Logistic regression analysis was used to test the primary hypothesis. A separate analysis tested whether there were differences by race and ethnicity during the delta variant phase of the pandemic. Patients: All hospitalized patients with COVID-19 who were above 17 years old were categorized by race and ethnicity as Black, Hispanic, Asian, White, Other, and Unknown. Main Measures: In-hospital mortality for patients with a known hospital outcome formed the primary outcome measure. Race and ethnicity were the primary independent variables. Key Results: There were 103,702 in-hospital Covid-19 admissions with 14,207 (13.7%) hospital deaths. Unadjusted in-hospital mortality for White patients was approximately 26% higher than for Black patients. After multivariable adjustment, none of the racial and ethnic groups had significantly different odds of in-hospital mortality compared to White patients. Only Hispanic patients had an odds ratio greater than one that was insignificant (OR = 1.06; 95% CI = 0.92-1.20). Findings for the delta variant phase were similar with the exception of the unknown category (OR = 1.90; 95% CI = 1.05-3.46). Conclusions: Disparities in-hospital mortality outcomes by race or ethnicity were not found in COVID-19 patients hospitalized in AMCs. AMCs are expected to lead health delivery systems in eliminating disparities associated with structural racism. The null findings are consistent with the hypothesis of no difference in hospital outcomes by race or ethnicity in academic medical centers.